2021
DOI: 10.1002/cpdd.1008
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic, Safety, and Pharmacodynamic Properties of Teverelix Trifluoroacetate, a Novel Gonadotropin‐Releasing Hormone Antagonist, in Healthy Adult Subjects

Abstract: Teverelix trifluoroacetate is a decapeptide, gonadotropin‐releasing hormone antagonist that binds competitively and reversibly to gonadotropin‐releasing hormone receptors in the pituitary gland, resulting in immediate suppression of luteinizing hormone and follicle‐stimulating hormone, which in turn causes a very rapid decrease in testosterone production in the Leydig cells of the testes in men and in estradiol in the ovaries in women. This phase 1 clinical study was an open‐label, parallel‐design, single‐cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The data from these five Phase 2 clinical studies adds to the evidence from a Phase 1 clinical study that was conducted in older, healthy male subjects, showing that teverelix DP has a good safety profile and is well tolerated [18]. In the Phase 1 study, the maximum concentration and exposure generally increased in proportion to the various doses evaluated (i.e., 60, 90 and 120 mg SC single doses), while reductions in LH, FSH and testosterone were more prolonged with an IM administration (90 mg) compared an SC administration at the same dose [18]. Here, we found that the longest mean duration of castration was observed after SC dosing for 3 consecutive days, and that IM administration had a delayed onset of castration compared to SC administration.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The data from these five Phase 2 clinical studies adds to the evidence from a Phase 1 clinical study that was conducted in older, healthy male subjects, showing that teverelix DP has a good safety profile and is well tolerated [18]. In the Phase 1 study, the maximum concentration and exposure generally increased in proportion to the various doses evaluated (i.e., 60, 90 and 120 mg SC single doses), while reductions in LH, FSH and testosterone were more prolonged with an IM administration (90 mg) compared an SC administration at the same dose [18]. Here, we found that the longest mean duration of castration was observed after SC dosing for 3 consecutive days, and that IM administration had a delayed onset of castration compared to SC administration.…”
Section: Discussionmentioning
confidence: 85%
“…Due to the different milieu following IM injection-where there is a high degree of vascularization and less adipose tissue-induration is not an issue. Indeed, this different milieu explains the different PK profiles (late phase Tmax and Cmax) observed following SC versus IM administration [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, follicle-stimulating hormone (FSH) and luteinizing hormone (LH) are produced. FSH acts on Sertoli cells to enhance sperm production, while LH binds to Leydig cells to promote testosterone synthesis (MacLean et al, 2022). Previous research has indicated that alcohol consumption may negatively affect the efficiency of the endocrine system, including the HPG axis, thus inhibiting the production of LH and testosterone (Enebeli et al, 2022).…”
Section: Effects Of Different Treatments On Testicular Dna Content An...mentioning
confidence: 99%
“…The release characteristics differ significantly between the SC and IM routes. 28 Initial high levels of exposure are seen following IM injection but teverelix DP is eliminated within a relatively short period of time (6-8 weeks). Following SC injection of teverelix DP there is a much slower release over time and teverelix remains measurable in the blood for up to 12 months following a single 120-mg injection.…”
mentioning
confidence: 99%